Acute dermal toxicity and sensitization studies of novel nano‐enhanced UV absorbers. Issue 3 (14th July 2015) - Piasecka‐Zelga, Joanna; Zelga, Piotr; Górnicz, Magdalena; Strzelczyk, Paweł; Sójka‐Ledakowicz, Jadwiga
Abstract : Acute dermal toxicity and sensitization studies of novel nano‐enhanced UV absorbers: Joanna Piasecka ‐Zelga, et al . Institute of Occupational Medicine, Research Laboratory for Medicine and Veterinary Products in the GMP Quality System, Poland Background: Many employees working outside are exposed to the harmful effects of UV radiation. A growing problem is also sensitization to textile materials and allergic reactions to active compounds. Groups of inorganic UV blockers with nanoparticles may provide superior properties over organic UV absorbers with relatively less potential of provoking dermatitis. Objective: To assess acute dermal irritation and sensitization of nano UV absorbers. Materials & Methods: Five UV absorbers with nano‐sized particles (Z11, TiO2 – SiO2 [TDPK], TK44, TK11, A8G) and 2 vehicles (paste‐based on 10% PEG, and dispersion with 1% HEC) were tested. Acute dermal irritation was tested using group of 3 rabbits for each absorber. The sensitization study was carried out on groups of 15 guinea pigs for each tested textile with a UV absorber showing an Ultraviolet Protection Factor (UPF)>40. This research was designed according to OECD Test Guideline No. 404 and 406, and 21 rabbits and 60 guinea pigs were used in the study. Results: In acute dermal irritation, Z11and A8G modifiers and the analyzed paste gave results of 0.047 to 0.33 which classifies them as barely perceptible irritants, whereas the other analyzed modifiers and dispersion gave results of 0.00 and were classified as nonirritating. Only the textile with TK 11 did not have UPF>40. The analyzed barrier materials were classified as nonsenitizers (TDPK, A8G) or mild sensitizers (TK44, Z11). Conclusions: None of the analyzed materials or modifiers induced major skin reactions in animals. Therefore, they present low risk of provoking skin reactions in humans.